Effect of pore-size distribution in cathodic gas diffusion layers on the electricity generation of microbial fuel cells (MFCs). Issue 124 (30th November 2015) - Shi, Xinxin; Huang, Tinglin
Abstract : A simple approximate proportional relationship was found between the increases of electricity generation of microbial fuel cells and the volume fraction of mesopores in gas diffusion layers. Abstract : A simple approximate proportional relationship was found between the increases of electricity generation of microbial fuel cells and the volume fraction of mesopores in gas diffusion layers. More importantly, the underlying mechanism of the effect of pore-size distribution was explored in detail by introducing Knudsen gas transport theory.